Effet D’une Sollicitation En Face A Face Et D’un Contact Tactile Sur L’acception Du Don Du Sang : Une Evaluation Lors D’une Collecte En Milieu Universitaire - Guéguen, Nicolas; Sire, Virginie; Sire, Virginie (European Scientific Journal, ESJ, 2016)
The positive effect of touching on compliance with a request has been widely reported in the social psychology literature. However its effect on blood donation has never been tested. Yet, research found that many further compliance gaining procedures were not efficient with blood donation requests. University students were solicited to give blood during a special one-day drive. Solicitations were made through face-to-face interactions. During the solicitation some participants were lightly touched or not on the forearm. No difference was found between the two experimental groups in the number of participants who agreed to give blood. Such results show that tactile contact is not an effective technique for increasing compliance with a blood donation request, and confirm previous studies which found that other compliance-growth techniques are not effective with blood donation requests. However, if was found that, compared to previous blood campaigns conducted in the same setting, more blood donations were observed attesting that face to face solicitation of potential blood donors significantly increased donations.